A proposal for the definition of housing with EXPRESS - Bayer, Semih; TÜRKYILMAZ, EMRAH (My University, 2019)
This article describes how to use the EXPRESS language for the definition of an architectural product. To make this definition, EXPRESS language and ISO 10303 standards examined. A housing project in the BIM environment described as an example by EXPRESS. The results show that it is possible to make the desired calculations about the house with EXPRESS. The definition made with a project that is still in the design phase can determine whether the project provides the desired spatial conditions by making any calculations. Thus, quality and cost-effective projects can obtain.
Keywords: EXPRESS; Housing; BIM; ISO 10303